SOME ARRANGEMENT OF SHOCK DELIVERY IN THE 4TH GENERATION IMPLANTABLE CARDIOVERTER DEFIBRILLATOR (ICD) IMPLANTATION - NAKANO, H.; KOYANAGI, H.; HAYASHI, K.; AKIMOTO, T.; SHIIKAWA, A.; HIRATA, K. (Jinko Zoki, 1998)
Twenty-one 4th generation ICDs were implanted in our institute from April, 1995 to April, 1997. Two electrodes system in the 4th generation ICD often used the metallic housing of the ICD, so-called “Can” RV configulation. Two cases were required the change of the configulation of 2 electrodes (RV “Can”). In one of them, SVC lead was used together. In other 2 cases who had been removed of the 3rd generation ICDs with infection, new ICDs were implanted on the right chest wall. Induced VTs/vfs for DFT tests after implantation at the right side could be terminated by two-electrode system with low DFTs and impedances. The change of direction of shock delivery and the right chest wall implantation of the 4th generated ICD did not influence the impedance at defibrillation. The 4th generated ICD might be efficacious for treating life threating arrhythmias in the place of the 3rd generation ICD requiring the subcutaneous patch electrode and inclease the flexibility of site of implantation.